Success and failure of dead‐time models as applied to hybrid pixel detectors in high‐flux applications. (8th February 2013) - Sobott, B. A.; Broennimann, Ch.; Schmitt, B.; Trueb, P.; Schneebeli, M.; Lee, V.; Peake, D. J.; Elbracht‐Leong, S.; Schubert, A.; Kirby, N.; Boland, M. J.; Chantler, C. T.; et al.
Abstract : The performance of a single‐photon‐counting hybrid pixel detector has been investigated at the Australian Synchrotron. Results are compared with the body of accepted analytical models previously validated with other detectors. Detector functionals are valuable for empirical calibration. It is shown that the matching of the detector dead‐time with the temporal synchrotron source structure leads to substantial improvements in count rate and linearity of response. Standard implementations are linear up to ∼0.36 MHz pixel −1 ; the optimized linearity in this configuration has an extended range up to ∼0.71 MHz pixel −1 ; these are further correctable with a transfer function to ∼1.77 MHz pixel −1 . This new approach has wide application both in high‐accuracy fundamental experiments and in standard crystallographic X‐ray fluorescence and other X‐ray measurements. The explicit use of data variance (rather than N 1/2 noise) and direct measures of goodness‐of‐fit (χ r 2 ) are introduced, raising issues not encountered in previous literature for any detector, and suggesting that these inadequacies of models may apply to most detector types. Specifically, parametrization of models with non‐physical values can lead to remarkable agreement for a range of count‐rate, pulse‐frequency and temporal structure. However, especially when the dead‐time is near resonant with the temporal structure, limitations of these classical models become apparent. Further, a lack of agreement at extreme count rates was evident.